2011
DOI: 10.1590/s0100-69162011000600006
|View full text |Cite
|
Sign up to set email alerts
|

Transpiração e temperatura foliar da cana-de-açúcar sob diferentes valores de potencial matricial

Abstract: RESUMO:O objetivo deste trabalho foi avaliar a variação diurna da transpiração e da temperatura foliar da cana-de-açúcar, cv. RB867515, sob diferentes potenciais matriciais de água no substrato de cultivo e as condições meteorológicas em ambiente protegido. O efeito do estresse hídrico na transpiração e temperatura foliar foi determinado a partir da suspensão da irrigação, quando foram realizadas três campanhas de medições, iniciadas aos 122; 150 e 185 dias após o plantio (DAP) até que o potencial matricial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 14 publications
1
19
0
11
Order By: Relevance
“…Trentin et al (2011) observed that leaf temperature is closely associated with the process of transpiration. As it increases, there is a reduction in leaf temperature due to the dissipation of energy in the form of latent heat.…”
Section: Resultsmentioning
confidence: 99%
“…Trentin et al (2011) observed that leaf temperature is closely associated with the process of transpiration. As it increases, there is a reduction in leaf temperature due to the dissipation of energy in the form of latent heat.…”
Section: Resultsmentioning
confidence: 99%
“…A cana-de-açúcar (Saccharum spp L.) destaca-se como uma das principais culturas de interesse econômico para o Brasil, fornecendo matéria-prima para a produção de açúcar, etanol e energia (TRENTIN et al, 2011) e pela eficiência na produção de biocombustíveis. Com destaque para o estado de São Paulo, tendo a maior área e a maior produção no país, 5,4 milhões de hectares e mais de 400 milhões de toneladas, respectivamente (AGRIANUAL, 2015).…”
Section: Introductionunclassified
“…When the mentioned variables have higher values, as observed at 97 and 105 DAP, favorable conditions are established for intensification of the crop evapotranspiration Trentin et al 2011). In the specific case of these days, the values of Tair, VPDair and Rg were generally higher in the period between 11 a.m. and 2 p.m.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, there are few researches carried out to evaluate the effect of salinity on sugarcane evapotranspiration. Trentin et al (2011) evaluated the effect of water stress on RB867515 cultivar at 125 DAP, verifying reductions in plant transpiration in relation to non-stress treatment, of 28.1 and 63.3% for the matrix potentials around -474 and -1272 kPa, respectively. The value of 28.1% is very close to the average reduction of 29% in ETcd, verified for the four cultivars in the this experiment, corresponding to the salinity increase from 3 to 9 dS m -1 , the last value being estimated through the equations shown in Figure 3.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation